The Strategy for Developing Siguntang Hill as A Pilgrimage Tourist Attraction in Palembang City - Mulyani, Irma; Nurbaeti; Ingkadijaya, Rahmat; Permatasari, Mustika; Aldora, Mega (Politeknik Pariwisata NHI Bandung, 2024)
Siguntang Hill is a small hill or the highest point in Palembang City with an altitude of 26 meters above sea level. It has historical significance from the royal period found in Palembang City and has various potential as a pilgrimage tour because there are 7 tombs located there. However, the condition of the tombs has deteriorated, and many buildings are not suitable for visiting. The purpose of this research is to review and analyze the management and development strategies of tourist attractions in Siguntang Hill as pilgrimage tourism. The research method used is a qualitative method with a descriptive approach, with data collection techniques in the form of documentation studies, observations, and interviews. The results of the study explain that the strengths of Bukit Siguntang include its central location in the city, accessibility via various transportation fleets, beautiful and cool panorama, and the presence of a King's Tomb which is an icon on Siguntang Hill. The weaknesses include the poor condition of the tombs, lack of human resources in the field of tourism, and limited physical resources for the development and management of facilities at Siguntang Hill. The opportunities include the support of the central government to make Siguntang Hill more attractive, hosting the Siguntang festival activities held regularly every year, and renovations to change the image of Siguntang Hill into a pleasant place to visit. The threats include the lack of dominance of pilgrimage tourism activities at Siguntang Hill, the emergence of competitors as tourist destinations in Palembang City, and the condition of the tombs eroded by time. Bukit Siguntang has significant potential as seen from the SWOT (IFAS and EFAS) analysis, with an IFAS matrix value of 1.7 and an EFAS matrix value of 1.3.